The freedom to choose: theory and quasi-experimental evidence on cash transfer restrictions - Sterck, O; Siu, J; Rodgers, C (Centre for the Study of African Economies, 2021)
Should cash transfer programmes restrict consumer choice? For example, should food assistance delivered in cash be restricted to food and exclude temptation goods? Theoretically, if transfers are extra-marginal, restrictions induce (1) a substitution effect away from restricted goods and (2) a negative wealth effect if transfer recipients resell unrestricted goods at a loss to access restricted goods. The welfare impact on transfer recipients is negative. We test and corroborate these predictions by exploiting a natural experiment in a refugee settlement in Kenya, where some refugees receive monthly cash transfers restricted to food while others get unrestricted cash transfers.